2003
DOI: 10.1124/jpet.103.057570
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Regulates Neuronal M2Muscarinic Receptor Function in the Ileum of Diabetic Rats

Abstract: Acetylcholine release from cholinergic nerves in the gastrointestinal tract is limited by neuronal M 2 muscarinic receptors. In diabetic animals, M 2 muscarinic receptor function in the ileum is increased, leading to decreased acetylcholine release and smooth muscle contraction in response to nerve stimulation. The mechanisms responsible for increased M 2 muscarinic receptor function are unknown but may contribute to the gastrointestinal dysmotility that occurs frequently in diabetics. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our data that insulin can inhibit M 2 receptors and that STZ reverses this effect are consistent with our previous studies showing that insulin depletion increases M 2 muscarinic receptor function and expression (30,40). In these previous studies, done in nonselected Sprague Dawley rats on a noncontrolled diet, increased function of M 2 receptor on airway nerves decreased the bronchoconstriction response to vagal stimulation, an effect we did not see in obese-resistant rats on a controlled diet.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our data that insulin can inhibit M 2 receptors and that STZ reverses this effect are consistent with our previous studies showing that insulin depletion increases M 2 muscarinic receptor function and expression (30,40). In these previous studies, done in nonselected Sprague Dawley rats on a noncontrolled diet, increased function of M 2 receptor on airway nerves decreased the bronchoconstriction response to vagal stimulation, an effect we did not see in obese-resistant rats on a controlled diet.…”
Section: Discussionsupporting
confidence: 81%
“…To test the direct effect of insulin on parasympathetic nerve-mediated airway smooth muscle contraction and M 3 muscarinic receptor function, human tracheal smooth muscle strips were suspended in organ baths in the absence and presence of insulin. Contractions were induced by electrical field stimulation (EFS) or by increasing concentrations of methacholine (MCh) as previously described (30). Neuronal M 2 muscarinic receptor function was tested in human tracheal smooth muscle by measuring the ability of gallamine, a selective antagonist, to potentiate EFSinduced contractions (19).…”
Section: Bronchoalveolar Lavage and Morphologic Study Of Lungmentioning
confidence: 99%
“…Altered signalling through the protein kinase C pathway in gastric myocytes may also contribute to diabetic gastroparesis 60 . Insulin can regulate the altered neuronal M2 muscarinic receptor function seen in the ileum of diabetic rats 61 . Recent studies have demonstrated that myopathy may play a role in diabetic gastroparesis.…”
Section: Mechanisms Underlying Diabetic Enteric Neuropathymentioning
confidence: 99%
“…58,59 Altered signalling through the protein kinase C pathway in gastric myocytes may also contribute to diabetic gastroparesis. 60 Insulin can regulate the altered neuronal M2 muscarinic receptor 61 Recent studies have demonstrated that myopathy may play a role in diabetic gastroparesis. A reduction in insulin/ IGF-I signalling in diabetes causes ICC depletion, subsequent stem cell factor depletion and resultant smooth-muscle atrophy.…”
Section: Alteration In Intestinal Muscle Contractilitymentioning
confidence: 99%
“…6 In diabetic rats, insulin regulates neuronal M 2 muscarinic receptor function in the ileum, suggesting that lack of insulin may lead to gastrointestinal dysmotility. 7 Differences in gastric emptying between non-insulindependent diabetes mellitus (NIDDM) and insulindependent diabetes mellitus (IDDM) have been reported, but the exact mechanism is not well evaluated. Cross-sectional studies of patients with long-standing (>∼3 years' duration) diabetes mellitus indicate that gastric emptying of solid or liquid meals is delayed in about 50% of cases and that the prevalence of delayed emptying in IDDM 1,8,9 and NIDDM 10,11 is similar.…”
Section: Introductionmentioning
confidence: 99%